Jobs and Exposure to International Trade within the Service Sector in Sweden - Kent Eliasson; Pär Hansson; Markus Lindvert (Örebro University School of Business, 2010)
The service sector is very heterogeneous with respect to internationalization; in some industries there is international trade (or it may potentially exist), whereas other industries are non-tradable. Data on international trade in services is, however, typically very limited, making it difficult to identify in which industries there are international trade. In this paper, we partially surmount the problems with insufficient service trade statistics by calculating locational Ginis for different industries in the private business sector as well as in the public sector. The basic idea is that from the regional concentration of different activities within a country one can identify industries where there appears to be regional trade, and hence also a potential for international trade. Based on our method we find that the number of employed in tradable service appears to be at least as large as in the manufacturing sector. Remarkably, a larger share of the skilled labor exposed to international trade is working in the service sector than in manufacturing, while a majority of the less skilled labor working in tradable industries is employed in manufacturing. When it comes to employment growth, we observe that the employment has increased in tradable service, while it has fallen in the manufacturing sector (the whole sector is regarded as tradable).
Keywords: F16; J44; R12; 330; jobs; service trade; regional concentration; structural change